Effect of flavonoids on the arachidonic acid metabolism - Silva, Rosimar R. da; Oliveira, Tânia T. de; Nagem, Tanus J.; Leão, Maria A. (Medicina (Ribeirao Preto), 2002)
The products of the ciclooxigenase and lipoxigenase action’s on the arachidonic acid are: prostaglandins, tromboxans and leucotriens, which are denominated eicosanoids. These compounds are homeostatic agents. They are involved in the integrity of the inflammatory, cardiovascular and renal systems. It has been demonstrated that flavonoids shows several pharmacological activities among them antiinflamatory and hipocholesterolemic properties. They reduce the risk of cardiovascular diseases and one of its principal action mechanism involve the inhibition of the enzymes which are involved in the final metabolism of the arachidonate.